2014
DOI: 10.1097/01.mnh.0000437611.42417.7a
|View full text |Cite
|
Sign up to set email alerts
|

The osteoprotegerin/tumor necrosis factor related apoptosis-inducing ligand axis in the kidney

Abstract: See the Video Supplementary Digital Content 1 (http://links.lww.com/CONH/A5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Consistent with it, it has been recently reported that elevated OPG is associated with increased 5- and 10-year risk of rapid renal decline, renal disease hospitalization, and/or deaths in elderly women [27]. Overall, these studies, mostly carried out in diabetic patients, suggest that OPG could be a biomarker for CKD progression, as reviewed in [28, 29]. Nevertheless, it remains unclear whether a similar association is present also in hypertensive patients.…”
Section: Introductionmentioning
confidence: 69%
“…Consistent with it, it has been recently reported that elevated OPG is associated with increased 5- and 10-year risk of rapid renal decline, renal disease hospitalization, and/or deaths in elderly women [27]. Overall, these studies, mostly carried out in diabetic patients, suggest that OPG could be a biomarker for CKD progression, as reviewed in [28, 29]. Nevertheless, it remains unclear whether a similar association is present also in hypertensive patients.…”
Section: Introductionmentioning
confidence: 69%
“…Candido (2014) reported that retention of peptides like OPG associated with renal impairment may provide part of the explanation. Additionally, inflammation, observed in patients with renal injury, drives the expression of OPG.…”
Section: Figmentioning
confidence: 97%
“…Thus, it is controversial whether RANKL acts on RANK to protect podocytes from apoptosis. In our opinion, RANKL may exert its anti-apoptotic effect on PAN-induced podocytes by binding the decoy receptor osteoprotegerin (OPG) (Blazquez-Medela, Lopez-Novoa, & Martinez-Salgado, 2011), which acts as a survival factor for endothelial cells (Malyankar et al, 2000), pancreatic β-cells (Schrader et al, 2007) and tubular cells (Candido, 2014;Lorz et al, 2008). Contrary to the findings of Liu et al, Stefan Kiechl et al (Kiechl et al, 2013) found that RANKL was a significant and independent risk predictor of type 2 diabetes mellitus, and when they blocked RANK, the RANKL-mediated upregulation of NF-κB activation and proinflammatory genes was completely inhibited.…”
Section: Discussionmentioning
confidence: 97%